Einige Eigenschaften der Funktionen, die keine nullgleiche dividierte Differenz besitzen - Kirjatsky, E. (Lithuanian Mathematical Journal, 1962)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: Э. Г. Кирьяцкий, Некоторые свойства функций, разделенная разность которых не равна нулю E. Kirjackis, Funkcijų, kurių padalytas skirtumas nėra lygus nuliui, kai kurios savybės